Formulation and pharmaceutical development of quetiapine fumarate sustained release matrix tablets using a QbD approach - Gavan Alexandru; Porfire Alina; Marina Cristina; Tomuta Ioan (Acta Pharmaceutica)
The main objective of the present study was to apply QbD methodology in the development of once-a-day sustained release quetiapine tablets. The quality target product profile (QTPP) was defined after the pharmaceutical properties and kinetic release of the innovator product, Seroquel XR 200 mg. For the D-optimal experimental design, the level and ratio of matrix forming agents and the type of extragranular diluent were chosen as independent inputs, which represented critical formulation factors. The critical quality attributes (CQAs) studied were the cumulative percentages of quetiapine released after certain time intervals. After the analysis of the experimental design, optimal formulas and the design space were defined. Optimal formulas demonstrated zero-order release kinetics and a dissolution profile similar to the innovator product, with f2 values of 74.53 and 83.74. It was concluded that the QbD approach allowed fast development of sustained release tablets with similar dissolution behavior as the innovator product.